Maternal bodies: redefining motherhood in early America - Doyle, Nora (University of North Carolina Press, 2018)
This new approach to the history of motherhood examines the role the female body played in defining motherhood from the mid-eighteenth century through the first half of the nineteenth century, demonstrating that physical representations or perceptions of the body were crucial to defining motherhood in different ways both for mothers themselves and for American culture at large.